SURVEI TINGKAT KETERAMPILAN DASAR BERMAIN FUTSAL PESERTA EKSTRAKULIKULER FUTSAL DI SMK PGRI 2 GENENG - Choir Ilham Irfan Andriyanto; Kuncoro Darumoyo; Arief Nur Wahyudi (Dharmas Journal of Sport, 2023)
Extracurriculars are learning activities outside of learning hours that are listed in the school program according to the circumstances and needs of the school. The purpose of this research is to determine the level of basic skills in playing futsal for students of SMK 2 PGRI Geneng. The location of this research was carried out on Jl. Geneng-Ngawi, Tejo, Keniten, Kec. Geneng, Ngawi Regency. This research is a type of quantitative descriptive research using a survey method with only one variable. The sample in this study were 16 futsal extracurricular students. Data analysis in this study used tests and measurements. The test instrument used in this study was divided into 4 points, each post carrying out different tests, while the tests and measurements included Dribble, Passing without controlling, Rotating 2 cones, Passing with controlling, Shooting the goal ball. The calculation of this test is to use the fastest time in carrying out the test from post one to post four. The results of this study are in the Very Good category 0 students (0%), stated in the Good category 5 students (31.25%), Enough category 6 Students (37.5%), Less category 4 students (25%), Poor category Once 1 student (6.25%). From these results the overall average score is 69.50 at the 68-71 level, so the skill level of playing futsal for extracurricular futsal students at SMK PGRI 2 Geneng is in the Enough category.